2017
DOI: 10.1038/onc.2016.414
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-218 contributes to epithelial–mesenchymal transition and tumor metastasis in lung cancer by targeting Slug/ZEB2 signaling

Abstract: Epithelial–mesenchymal transition (EMT) has been recognized as a key element of cell migration and invasion in lung cancer; however, the underlying mechanisms are not fully elucidated. Recently, emerging evidence suggest that miRNAs have crucial roles in control of EMT and EMT-associated traits such as migration, invasion and chemoresistance. Here, we found that miR-218 expression levels were significantly downregulated in lung cancer tissues compared with adjacent non-cancerous tissues, and the levels of miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 62 publications
3
104
0
Order By: Relevance
“…Previous studies have suggested that several miRNAs were abnormal expression in the progress of periodontal disease and regulated multifarious genes such as RUNX2, osteocalcin (OC), and EGFR (Motedayyen, Ghotloo, Saffari, Sattari, & Amid, ; Xie et al, ; Zhou et al, ). MiR‐218, a tumour suppressor, is significantly downregulated in various cancers (Deng et al, ; Shi et al, ) and inflammatory disorders (Xu et al, ). For example, the decrease of serum miR‐218 levels was observed in the inflammation induced by cigarette smoking, and miR‐218 overexpression would repress TNFR1‐mediated activation of NF‐κB and resulted in decreasing levels of serum IL‐6 and IL‐8 (Xu et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that several miRNAs were abnormal expression in the progress of periodontal disease and regulated multifarious genes such as RUNX2, osteocalcin (OC), and EGFR (Motedayyen, Ghotloo, Saffari, Sattari, & Amid, ; Xie et al, ; Zhou et al, ). MiR‐218, a tumour suppressor, is significantly downregulated in various cancers (Deng et al, ; Shi et al, ) and inflammatory disorders (Xu et al, ). For example, the decrease of serum miR‐218 levels was observed in the inflammation induced by cigarette smoking, and miR‐218 overexpression would repress TNFR1‐mediated activation of NF‐κB and resulted in decreasing levels of serum IL‐6 and IL‐8 (Xu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that several miRNAs were abnormal expression in the progress of periodontal disease and regulated multifarious genes such as RUNX2, osteocalcin (OC), and EGFR (Motedayyen, Ghotloo, Saffari, Sattari, & Amid, 2015;Xie et al, 2011;Zhou et al, 2016). MiR-218, a tumour suppressor, is significantly downregulated in various cancers (Deng et al, 2017;Shi et al, 2017) and inflammatory disorders .…”
Section: Mir-218 Decreased Bone Destruction and Inflammation In Ligmentioning
confidence: 99%
“…14,15 MicroRNAs, such as miR-494, miR-153 and miR-218, inhibited lung cancer development and metastasis via suppressing cellular proliferation, inhibiting cell migration and invasion and EMT. [16][17][18] Here, we found that B3GNT3 was overexpressed in lung cancer and upregulated expression of B3GNT3 was associated with unfavorable prognosis of lung cancer patients. Silencing B3GNT3 inhibited lung cancer cell growth in vitro and suppressed lung tumor development in vivo.…”
Section: Introductionmentioning
confidence: 73%
“…MiR-218 has been widely reported to be silenced in multiple human cancers, and function as a putative tumor suppressor, including gastric, nasopharyngeal, lung, cervical, oral and brain tumors [9][10][11][35][36][37][38][39]. Besides, glioma patients with low miR-218 expression had poorer disease-free survival and overall survival [12].…”
Section: Discussionmentioning
confidence: 99%